Synthesis of isatin, 5-chloroisatin and their 2-1,3,4 oxadiazoline derivatives for comparative cytotoxicity study on brine shrimp - Md. Rabiul Islam and Mohammad Mohsin (Bangladesh Pharmacological Society, 2007)
Isatin (3a), isatin 3-carbohydrazone (4a), 5-spiro (isatin) 2-(N-acetyl hydrazino) 4-(N-acetyl)-2-1,3,4 oxadiazoline (5a), and 5-spiro (isatin) 2-hydrazino-2-1,3,4 oxadiazoline (6a) have been synthesized from unsubstituted oximinoacetanilide (2a). 4-Chlorooximinoacetanilide (2b), 5-chloroisatin (3b), 5-chloroisatin 3-carbohydrazone (4b) and 5-spiro (5-chloroisatin) 2-(N-acetyl hydrazino) 4-N-acetyl 2-1,3,4 oxadiazoline (5b) compounds have been synthesized from p-chloroaniline. The structures of the products have been characterized from spectral analysis and comparative cytotoxicity study of them was studied.